Let's make African research discoverable, together - Havemann, Johanna; Ogot, Madara; Nyirongo, Revelation (My University, 2023)
Presentation held at the Science Granting Councils Initiative (SGCI) 2023 Annual Forum and Global Research Council (GRC) Sub-Saharan Africa Regional Meeting, which took place from November 13th to 17th in Mombasa, Kenya.
Keywords: Science Granting Councils Initiative; Global Research Council; Kenya